2021
DOI: 10.23876/j.krcp.21.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal saline solution with low-chloride solutions in renal transplants: a meta-analysis

Abstract: Background: Normal saline solution (NSS) has been the fluid of choice for renal transplant patients, but it can lead to hyperchloremic acidosis and hyperkalemia. This study was performed to compare the safety profile of low-chloride solutions with that of NSS in renal transplant patients. Methods: We conducted a systemic review search on PubMed, Embase, and the Central Cochrane Registry. Randomized clinical trials (RCTs) and matched cohort studies involving NSS as the control arm and low-chloride solutions as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our results on end-of-surgery acid-base and electrolyte measures are consistent with previous metaanalyses in the context of better balance achieved with the administration of balanced crystalloids. 10,11 The end of surgery chloride and pH also support the evidence that normal saline promotes a higher chloride concentration and, consequently, hyperchloremic metabolic acidosis, 6 which has been linked with adverse outcomes in renal transplant patients. 42 Despite the hypothesis of an increased risk of hyperkalemia, end-of-surgery potassium level was not significantly different between the groups analyzed.…”
Section: Anesthesia and Analgesiamentioning
confidence: 71%
See 1 more Smart Citation
“…Our results on end-of-surgery acid-base and electrolyte measures are consistent with previous metaanalyses in the context of better balance achieved with the administration of balanced crystalloids. 10,11 The end of surgery chloride and pH also support the evidence that normal saline promotes a higher chloride concentration and, consequently, hyperchloremic metabolic acidosis, 6 which has been linked with adverse outcomes in renal transplant patients. 42 Despite the hypothesis of an increased risk of hyperkalemia, end-of-surgery potassium level was not significantly different between the groups analyzed.…”
Section: Anesthesia and Analgesiamentioning
confidence: 71%
“…8,9 However, the administration of these fluids has not yet been standardized during kidney transplant as it has been suggested that they could lead to hyperkalemia due to their higher potassium concentration. 5 Furthermore, 2 previous meta-analyses 10,11 while indicating an improved postoperative electrolyte and acid-base balance in patients receiving balanced crystalloids, did not demonstrate significant clinical differences, such as a reduction in DGF.…”
mentioning
confidence: 90%
“…Previous evidence shows that balanced fluid (lactated/acetated Ringer’s solution (LR/AR) or acetate-based Plasma-Lytes) is advantageous over NS in critically ill adults ( 7 , 8 ), specifically in patients with diabetic ketoacidosis ( 9 ). However, recent findings with a large sample of patients reveal that balanced crystalloids (LR and AR) do not have advantages over NS regarding hospital-free days in non-critically ill patients ( 10 ) and that balanced fluids show no significant superiority over NS in reducing 90-day mortality in critically ill patients and kidney transplant graft function ( 11 , 12 ). To date, the clinical outcomes of various fluids are still controversial in this respect, and one of the beneficial effects of current fluids may depend on specific subgroups of patient populations.…”
Section: Non-optimality Of Current Fluidsmentioning
confidence: 99%
“…Most studies concerning the in vivo effects of infused solutions on coagulopathy were based on 0.9% sodium chloride solution or hydroxyethyl starches (HES), which are currently used less frequently due to known adverse effects [ 9 ]. Normal saline solution (0.9% NaCl; NS) infused in large volumes needed for fluid resuscitation leads to hyperchloremic acidosis [ 10 ]. HES solutions were reported to cause kidney injury and increased the need for dialysis in two large-scale randomized controlled trials [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%